Updates in prevention policies of early-onset group B streptococcal infection in newborns - Yao Zhu; Xin-Zhu Lin (Pediatrics and Neonatology)
Invasive disease owing to group B Streptococcus (GBS) is a major cause of illness and death among newborns. Maternal GBS colonization of gastrointestinal tract and/or vagina is the primary risk factor for neonatal GBS early-onset disease (EOD). In Europe and America, there are marked declines in neonatal GBS-EOD through widespread implementation of guidelines for maternal GBS screening and subsequent intrapartum antibiotic prophylaxis (IAP). The key measures necessary for prevention of GBS-EOD include correct specimen collection and processing, nucleic acid amplification testing (NAAT) for GBS identification, regimens for mothers with premature rupture of membranes (PROM), preterm labor or penicillin allergy, and coordination between obstetrics and pediatrics. Antibiotic prophylaxis has some disadvantages, so researchers should develop other preventive measures. Maternal vaccines to prevent perinatal GBS infection are currently under development. However, as large, population-based sampling studies are rarely conducted, the colonization rate and the disease burden of GBS in perinatal period are poorly understood in developing countries. The harm of GBS to newborns has been recognized in recent years in mainland China, but authorized prevention measures are still lacking. In order to enhance the understanding of GBS-EOD prevention, the most recent guidelines updates by the American College of Obstetricians and Gynecologists (ACOG) and American Academy of Pediatrics (AAP) in 2019–2020 are summarized in this article.